Multiple unerupted mandibular permanent molar teeth: a case report - Aydan Açıkgöz; Bora Özden; Burcu Baş; Kaan Gündüz (Cumhuriyet University, 2012)
The multiple impacted teeth at jaws are a rare condition that frequently associated with syndromes, metabolic disorders or trauma. A 48-year old male patient was referred to our clinic, with complaint of pain on right retromolar region while chewing. The patient had facial asymmetry and restricted mouth opening. Clinical and radiographic examination revealed the impaction of mandibular first, second and third molar and an abnormal condyle and coronoid process. All of the impacted teeth were extracted. Because the patient refused other treatment procedures no surgical intervention was performed for the asymmetry and restricted mouth opening. Six months clinic and radiographic follow up were satisfactory.